- Imagine A Proposal to Implementation The Quality Management System ISO 9001: 2008 - Consultation to Department of Student Activities in The Department of Education in Riyadh - Al Muhaysa, Nisreen Abdullah (Journal of Economic, Administrative and Legal Sciences, 2018)
The goals of this study is centered to present a suggested picture on how to enforce a department of quality system (ISO), and how much it was accepted by employees to administer it in the department.          The researcher used analytical descriptive curriculum for her study. The study society and sample consists of female employees in the Department of Student's Activities. A survey was also used as a tool for their opinion to implement the importance quality management system to ease administrative work.            The study came to a conclusion that most of the staff give the administration moderate rating. It is important, in their opinion, to upgrade the administration process and apply quality management system. The certificate isn’t as important to them as it proves the absence of resistance to apply the system; even if they don’t receive the certificate because it’s expensive. The study did not find statistically significant differences (α≤0.05) between the responses of employees on the application of quality management system in the management of student activity due to the personal and functional variables (scientific qualification_ job).           The researcher made recommendations to the administration one of which training the staff, turning to an electronical system. And, adopt the stages of the suggested picture to implement the quality management system and obtain a certificate of conformity.
Keywords: quality; quality management system; ISO; female student activity management; Ministry of Education; General Administration of Education in Riyadh